PEMANFAATAN KEKAYAAN INTELEKTUAL KOMUNAL (KIK) UNTUK PENGEMBANGAN EKONOMI KREATIF - Siswoyo, Amelia Anggriany (Lex Lectio Law Journal, 2024)
AbstractThe utilization of Communal Intellectual Property (Communal IP) has become one of the important strategies in the development of the creative economy in Indonesia. The main focus of this study is on the importance of Communal IP utilization in boosting the creative economy, as well as effective strategies and management models to protect and develop Communal IP. Using a comparative analysis approach, this study investigates how to utilize cultural heritage: Communal IP in Indonesia to drive creative economy growth. The results show that one of the models of commercial utilization of Communal IP is the benefit-sharing model, where the benefit-sharing model is also stated in Article 33 of Government Regulation No. 56 of 2022 on Communal Intellectual Property. Effective integration between Communal IP and modern innovation can create significant economic opportunities while preserving cultural heritage values.AbstrakPemanfaatan Kekayaan Intelektual Komunal (KIK) telah menjadi salah satu strategi penting dalam pengembangan ekonomi kreatif di Indonesia. Fokus utama penelitian ini adalah pada pentingnya pemanfaatan KIK dalam meningkatkan ekonomi kreatif, serta strategi dan model pengelolaan yang efektif untuk melindungi dan mengembangkan KIK. Dengan menggunakan pendekatan analisis komparatif, studi ini menyelidiki bagaimana cara memanfaatkan warisan budaya:KIK di Indonesia untuk mendorong pertumbuhan ekonomi kreatif. Hasil penelitian menunjukkan bahwa salah satu model pemanfaatan KIK secara komersial adalah dengan model pembagian manfaat (benefit-sharing), dimana model pembagian manfaat (benefit-sharing) juga tercantum dalam Pasal 33 Peraturan Pemerintah Nomor 56 Tahun 2022 Tentang Kekayaan Intelektual Komunal. Integrasi yang efektif antara KIK dan inovasi modern dapat menciptakan peluang ekonomi yang signifikan, sambil melestarikan nilai-nilai warisan budaya.